2015
DOI: 10.1016/j.jbiomech.2015.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and shear stress in trabecular bone marrow during whole bone loading

Abstract: Skeletal adaptation to mechanical loading is controlled by mechanobiological signaling. Osteocytes are highly responsive to applied strains, and are the key mechanosensory cells in bone. However, many cells residing in the marrow also respond to mechanical cues such as hydrostatic pressure and shear stress, and hence could play a role in skeletal adaptation. Trabecular bone encapsulates marrow, forming a poroelastic solid. According to the mechanical theory, deformation of the pores induces motion in the fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 57 publications
(74 reference statements)
2
30
0
Order By: Relevance
“…In addition to the bone morphology, Yamada had found that the different distribution of cartilage on trochlear sulcus in patients with and without recurrent patellar dislocation [41]. Moreover, the previous studies had proved the abnormalities of trabecular under abnormal mechanical stress [42]. In this study, researchers found similar changes at different levels.…”
Section: Discussionsupporting
confidence: 55%
“…In addition to the bone morphology, Yamada had found that the different distribution of cartilage on trochlear sulcus in patients with and without recurrent patellar dislocation [41]. Moreover, the previous studies had proved the abnormalities of trabecular under abnormal mechanical stress [42]. In this study, researchers found similar changes at different levels.…”
Section: Discussionsupporting
confidence: 55%
“…This would further suggest that the load duration-related response could be strain magnitude dependent, with bone tissues that are subjected to lower peak strains reaching a load duration saturation at fewer load cycles than tissues subjected to greater strain magnitudes. It is also possible that the cellular mechanisms of the cancellous and cortical bone tissues’ responses to mechanical loading could be different [38] due to differences in their biological microenvironment [39, 40]. Another possibility is that longer loading durations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, shear stress in trabecular bone during whole bone loading produces micro-scale interaction between bone marrow and trabecular bone. It affects the distribution of mechanical stress and strain in bone marrow and its cellular components, e.g., hematopoietic stem cells, osteoclasts, pre-osteoclasts, and macrophages [91]. Tatsumi et al [92•] developed a mouse model in which ~ 80% of the osteocytes are ablated upon injection with diphtheria toxin.…”
Section: Physical Niche Conditions Of (Early) Osteocytes and Myoblastsmentioning
confidence: 99%